EFEKTIVITAS PENAMBAHAN TEPUNG TEMULAWAK (Curcuma Xanthorrhiza roxb) dan TEPUNG TEMU PUTIH (Curcuma Zedoaria roxb) DALAM RANSUM KOMERSIAL TERHADAP PERFORMANS AYAM PEDAGING - Bayoa, Dian L. M Bayoa; Sarayar, C L; Najoan, Marie; utiah, wapsiati (ZOOTEC, 2014)
An experiment was conducted to examine the effectiveness of Curcuma Xanthorrhiza roxb and Curcuma Zedoaria rox flours added in ration on performances of broilers. Fifty-four CP-707Â® strain broilers were used in the experiment at animal house of Animal Husbandry Faculty, Sam Ratulangi University, Manado and they were placed into cages (60cm x 45cm x 45cm), three birds per cage. Randomized completely design were used in this experiment, with three treatments and six replications. The three treatments were R0 (ration without Curcuma Xanthorrhiza roxb and Curcuma Zedoaria rox flours), R1 (Ration with 2% of Curcuma Xanthorrhiza roxb flour) and R2 (Ration with 2% of Curcuma Zedoaria rox flour). It was found that, there were no significant different (P>0.05) between treatments on feed consumption, body growth and feed conversion ratio of broilers. Feed consumptions were 111,69gram/bird/day (R0), 118,98gram/bird/day (R1), and 124,34gram/bird/day (R2); Body growths were 53,09gram/bird/day (R0), 54,84gram/birdr/day (R1), 57,59gram/bird/day (R2); Feed conversion ratios were 2,20gram/bird/day (R0), 2,18gram/bird/day (R1), and 2,16gram/bird/day (R2) respectively. It was concluded that, the performances of broilers given ration with addition of 2% of Curcuma Xanthorrhiza roxb and Curcuma Zedoaria rox flours were same as the performances of broiler given ration without Curcuma Xanthorrhiza roxb and Curcuma Zedoaria rox flours Curcuma Xanthorrhiza roxb and Curcuma Zedoaria rox flours. Key words: Broilers, Curcuma Xanthorrhiza roxb, Curcuma Zedoaria rox, flour.